2008
DOI: 10.1136/bmj.a2261
|View full text |Cite
|
Sign up to set email alerts
|

Test, episode, and programme sensitivities of screening for colorectal cancer as a public health policy in Finland: experimental design

Abstract: Objectives To report the sensitivities of the faecal occult blood test, screening episode, and screening programme for colorectal cancer and the benefits of applying a randomised design at the implementation phase of a new public health policy.Design Experimental design incorporated in public health evaluation using randomisation at individual level in the target population.Setting 161 of the 431 Finnish municipalities in 2004-6.Participants 106 000 adults randomised to screening or control arms. In total, 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 23 publications
(28 reference statements)
5
72
1
2
Order By: Relevance
“…Interaction between gender and FHbC level either with ordinal or continuous data type was also tested as the previous study has shown the sensitivity of guaiac fecal occult blood test (gFOBT) was poorer in females than males. 22,23 Because of the early detection of colorectal cancer or adenoma for those with FHbC 100 ng/ ml (via referral for colonoscopy), we adjusted the time to event for these cases by a correction factor, the overall follow-up time divided by average interval from age of 30 years to age at first screen in this cohort (please see the Supporting Information Appendix for further details). The regression coefficients from the AFT models were taken as clinical weights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between gender and FHbC level either with ordinal or continuous data type was also tested as the previous study has shown the sensitivity of guaiac fecal occult blood test (gFOBT) was poorer in females than males. 22,23 Because of the early detection of colorectal cancer or adenoma for those with FHbC 100 ng/ ml (via referral for colonoscopy), we adjusted the time to event for these cases by a correction factor, the overall follow-up time divided by average interval from age of 30 years to age at first screen in this cohort (please see the Supporting Information Appendix for further details). The regression coefficients from the AFT models were taken as clinical weights.…”
Section: Discussionmentioning
confidence: 99%
“…Finnish also reported higher test sensitivity in men than women using incident cancer data from their colorectal cancer screening program. 23 Studies for different cutoff values by gender are worthy of being investigated by the application of our gender-specific predictive model in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in the screening group were mailed a gFOBT test at intervals of 2 years. The Finnish program shows a high level of compliance of the target population (70.8%), particularly for females [33] . In the Netherlands, the optimum screening strategy is still being developed.…”
Section: Crc Screening In Europementioning
confidence: 99%
“…Individuals in the screening group were mailed a gFOBT test at intervals of 2 years. The finish program shows a high level compliance of the target population (70.8%), particularly for females [9] Poland is the only state at the moment using colonoscopy as the only screening method, without the alternative of of FOBTs. An opportunistic screening programme was initiated in 2000, and by 2005, this had grown to 57 centres across Poland.…”
Section: Current Tests For Colorectal Screening and Emerging Screeninmentioning
confidence: 99%